Teaching EFLLs Listening Subskills With a Speaking-Listening Model in a Computer-Mediated Communication Setting - Zhao, Jinman; Lee, Chang In (Frontiers in Psychology, 2022)
The purpose of this study is to explore the impact of teaching subskills, namely micro and macro-skills, with a speaking-listening model on the improvement of listening competence. The research included 112 Chinese tertiary students with intermediate English proficiency who were recruited from around the country. Before attending a listening class, the experimental group engaged in oral practice of the sub-skills, while the control one engaged in conventional listening-oriented preparation before attending a listening class. A randomized controlled trial (RCT), as well as a questionnaire, were used to assess listening skills. Following the results of the test analysis, we came to the conclusion that practicing listening sub-skills, first verbally and subsequently audibly, had a substantial impact on the development of listening competence. This efficiency was particularly evident when it came to growing discourse and pragmatical listening skill, rather than to developing grammatical and sociolinguistic competence. The results of the questionnaire indicated that there was minimal difference between the two groups in terms of listening strategic competence. Our findings were confirmed by coding the interview data, which revealed that tertiary students' self-agency and class participation had increased. The findings indicate that teaching tertiary students listening with speaking before listening in a computer-mediated communication (CMC) setting has an uneven influence on their development of listening skills.